2021
DOI: 10.1055/a-1401-2716
|View full text |Cite
|
Sign up to set email alerts
|

Total Mycosynthesis: Rational Bioconstruction and Bioengineering of Fungal Natural Products

Abstract: Total biosynthesis in fungi is beginning to compete with traditional chemical total synthesis campaigns. Advantages, disadvantages and future opportunities are discussed within the scope of several recent examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 109 publications
0
11
0
Order By: Relevance
“…We, [20,21] and others, [22] have shown that reconstruction of cryptic fungal biosynthetic pathways in the host organism Aspergillus oryzae NSAR1 is an effective way to understand complex transformations. Here, we deploy those methods and in vitro studies of isolated enzymes aiming to overcome the hurdles that have previously hampered characterization of pathway intermediates during the biosynthesis of these intriguing metabolites [3] …”
Section: Introductionmentioning
confidence: 99%
“…We, [20,21] and others, [22] have shown that reconstruction of cryptic fungal biosynthetic pathways in the host organism Aspergillus oryzae NSAR1 is an effective way to understand complex transformations. Here, we deploy those methods and in vitro studies of isolated enzymes aiming to overcome the hurdles that have previously hampered characterization of pathway intermediates during the biosynthesis of these intriguing metabolites [3] …”
Section: Introductionmentioning
confidence: 99%
“…oryzae is a highly useful host organism for the heterologous expression and engineering of fungal secondary metabolites. In particular, it has been extensively used for the production of fungal metabolites stemming from iterative type I PKS that use predominantly acetyl-CoA and malonyl-CoA for their construction [17]. Bacterial modular PKS, on the other hand, often use propionyl-CoA and methylmalonyl-CoA for the construction of polyketides [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…It has a generally regarded as safe (GRAS) status and is easily cultured in the lab, amenable to genetic modification using a variety of techniques, and is known for its high protein production. Recently, A. oryzae has proven itself to be an extremely capable host for heterologous expression of complete and partial fungal biosynthetic gene clusters (BGC), and for their systematic engineering [10][11][12][13][14][15][16][17]. A. oryzae does not produce significant amounts of its own secondary metabolites, meaning it is a clean host allowing facile detection and purification of heterologously produced compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Heterologous expression of its coding gene and of the upstream gene for the CYP450 AuAP450 in Aspergillus oryzae allowed the isolation of ve sesterterpene hydrocarbons, including aspergildienes A-D (115,117,119,121) and aspergiltriene (123). In addition, the CYP450 oxidation products aspergilols A-D (116, 118, 120, 122) were obtained.…”
Section: Heterologous Expression Of Sesterterpenoid Pathways In Asper...mentioning
confidence: 99%